AKIBAT HUKUM CERAI TALAK OLEH APARATUR SIPIL NEGARA BERDASARKAN UNDANG-UNDANG NOMOR 5 TAHUN 2014 TENTANG APARATUR SIPIL NEGARA DI PENGADILAN AGAMA PEKANBARU - sakti, Laras; Jayakusuma, Zulfikar; Fitriani, Riska (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
The life of the State Civil Apparatus (ASN) has been regulated in such a way, so that their daily life cannot be separated from the norms in the rules of labor law. Stipulation of Government Regulation No. 10/1983 jo. Government Regulation Number 45 of 1990 not only shows that the labor law does not only apply when a State Civil Apparatus (ASN) is in the office, but also outside the office. Efforts to improve the discipline of the State Civil Apparatus (ASN) related to exemplary and exemplary must be given to the State Civil Apparatus (ASN) to subordinates and the community, so that the State Civil Apparatus (ASN) is given high disciplinary provisions. To carry out marriage and divorce, the State Civil Apparatus (ASN) must first obtain permission from the official concerned.The formulation of the problem in this study is first, How is the implementation of divorce divorce carried out by the State Civil Apparatus based on Law Number 5 of 2014 concerning State Civil Apparatus at the Pekanbaru Religious Court and How is the legal certainty of the result of divorce by the State Civil Apparatus based on the Act? Number 5 of 2014 concerning State Civil Apparatus at the Pekanbaru Religious CourtThis type of research is a sociological legal research, namely research conducted by identifying the law and analyzing the relevant and applicable laws and regulations. As for in this study the author will go directly to the field to obtain data by using interviews.The implementation of divorce for the State Civil Apparatus is slightly different when filing for divorce where in filing for divorce there are different conditions where if the State Civil Apparatus wants to carry out a divorce, it must obtain permission from the official concerned where the State Civil Apparatus is located. determined, without which the divorce proceedings would continue. process, and a permit may follow before a decision is issued by the Assembly, if a permit has not been issued then a decision cannot be made. Keywords: Implementation, Divorce, State Civil Apparatus